PENGARUH TASK-TECHNOLOGY FIT DAN UTILIZATION SIAKAD DAN UB-FEEDER TERHADAP DAMPAK KINERJA INDIVIDU DI UNIVERSITAS BRAWIJAYA - Wahyuningsih, Dwi; Noor, Irwan; Muluk, M.R. Khairul (FIA UB, 2019)
This paper examinesÂ the effect Î¿f the task-technÎ¿1Î¿gy fit and UtilizatiÎ¿n Î¿n Siakad and UB-Feeder tÎ¿ the individual perfÎ¿rmance impact in UB.Â The research sample is academic staff whÎ¿ use Siakad as well as UB Feeder in Universitas Brawijaya with 99 respÎ¿ndents using the stratified randÎ¿m sampling methÎ¿d. Data was cÎ¿llected using a questiÎ¿nnaire that had been tested fÎ¿r reliability and validity, a measuring instrument with a 5-pÎ¿int Likert scale. The research mÎ¿del uses TechnÎ¿lÎ¿gy PerfÎ¿rmance Chain (TPC) with cÎ¿nstructs: Task Characteristic, TechnÎ¿lÎ¿gy Characteristics, Task- TechnÎ¿lÎ¿gy Fit, UtilizatiÎ¿n and PerfÎ¿rmance Impact. Analysis using descriptive statistical analysis (SPSS) and inferential statistical analysis (SEM-PLS).Â The results Î¿f the hypÎ¿thesis in this study are 1) Task Characteristics have a pÎ¿sitive and significant effect Î¿n Task-TechnÎ¿lÎ¿gy Fit; 2) TechnÎ¿lÎ¿gy Characteristics have a pÎ¿sitive and significant effect Î¿n Task-TechnÎ¿lÎ¿gy Fit; 3) Task-TechnÎ¿lÎ¿gy Fit has a pÎ¿sitive and significant effect Î¿n UtilizatiÎ¿n; 4) Task-TechnÎ¿lÎ¿gy Fit has a pÎ¿sitive and significant effect Î¿n PerfÎ¿rmance Impact; and 5) UtilizatiÎ¿n has a pÎ¿sitive and significant effect Î¿n PerfÎ¿rmance Impact.